2009
DOI: 10.1021/ma9020455
|View full text |Cite
|
Sign up to set email alerts
|

Linear Poly(ethylene imine)s by Acidic Hydrolysis of Poly(2-oxazoline)s: Kinetic Screening, Thermal Properties, and Temperature-Induced Solubility Transitions

Abstract: The kinetics for the acidic hydrolysis of two water-soluble poly(2-oxazoline)s with methyl and ethyl substituents were investigated. It could be observed that poly(2-ethyl-2-oxazoline) (PEtOx) and poly(2methyl-2-oxazoline) (PMeOx) are hydrolyzed following a linear relation with time. Various polymer lengths and concentrations were investigated, revealing that both parameters had no influence on the hydrolysis kinetics. Comparison between PEtOx and PMeOx revealed that the smaller PMeOx side group could be remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 37 publications
7
96
0
Order By: Relevance
“…Schubert, Hoogenboom and co-workers investigated the acid-mediated hydrolysis of pMeOx and pEtOx [208]. They found that the hydrolysis kinetics did not show significant dependency on polymer concentrations or polymerization degrees.…”
Section: Partial Hydrolysis: Copolymers Containing Units Of Peimentioning
confidence: 99%
“…Schubert, Hoogenboom and co-workers investigated the acid-mediated hydrolysis of pMeOx and pEtOx [208]. They found that the hydrolysis kinetics did not show significant dependency on polymer concentrations or polymerization degrees.…”
Section: Partial Hydrolysis: Copolymers Containing Units Of Peimentioning
confidence: 99%
“…Poly(ethylene imine) is an important polyelectrolyte within this class, and is known in two different forms [38,39]. Highly branched poly(ethylene imine) (BPEI) is obtained by ring-opening polymerization of ethylenimine and linear poly(ethylene imine) (LPEI) is synthesized by the hydrolysis of poly(2-oxazoline)s. These polyelectrolytes were investigated in substantial detail [31,38,[40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Polyethylenimine is a polyamine which possesses a high number of advantages, such as being a chelating agent, having good water solubility, and good physical and chemical stability and that can be easily obtained by oxazoline-based polymers hydrolysis. [20,21] Most of the studies of polymers with antimicrobial activity are based on compounds and materials possessing quaternary ammonium salts in their structure since its antimicrobial activity has been known for decades. [22][23][24] Waschinski and co-workers reported the synthesis of a series of oxazoline-based polymers, terminated with quaternary ammonium groups (using a series of Nalkyl-N,N-dimethylamines but also pyridine), prepared via standard CROP.…”
Section: Introductionmentioning
confidence: 99%